PERIODOGRAM ANALYSIS OF THE BRIGHTNESS VARIATIONS OF 8 RED SUSPECTED VARIABLES - Marsakova, V. I.; Rottar, S. V.; Andronov, I. L. (Одеські астрономічні публікації, 2017)
Eight red variables from the lists by Collins (1990, 1991) were measured on the plates of the Odessa plate collection. The results of the periodogram analysis are presented. TAV 0451+69 shows two oscillations with periods 242d and 152d. TASV 0714+39 shows 3 harmonic wave with P = 403.2d.